Analysis of 2 Evaluation Methods of Footprint: Hernandez Corvo Index Vs Cavanagh & Rodgers Arch Index [Análisis de Dos Métodos de Evaluación de la Huella Plantar: Índice de Hernández Corvo Vs. Arch Index de Cavanagh y Rodgers] - Sanchez-Ramirez, C (Ediciones Doyma, S.L., 2017)
Objective The objective of this research was to analyze two quantitative methodologies of evaluation of medial plantar longitudinal arch (MPLA) in a sample of Chilean active subjects. Material and method In a sample of 145 University students of both sexes of 19.36 years (±1.76) of age; 1.68 m (±0.09) of height; and 67.04 kg (±12.00) of body-mass is obtained the footprint from photo-podoscopy, which was analyzed according to the Arch Index (AI) and the Hernandez Corvo Index (HCI). Results The comparison between HCI and AI in a same foot generating significant differences in men, in the right (P<.0001, ES = 0.9577) and left (P<.0001, ES = 0.9560) feet. Women have significant differences in the right foot (P<.0001, ES= 0.9264) and also left (P<.0001, ES = 0.9314). Conclusions AI has been shown to be more appropriate than HCI in evaluating feet in this sample, given its consistency in describing areas of plantar support, and excluding the area of support of the toes. In addition, it was demonstrated that the original values used for the classification of the type of feet coincided with the values found in this sample. It is suggested to use AI in this population and their original classification. However, it is warned that women needed to expand the sample since in this group, there was a slight difference with the original values. © 2017 Asociación Española de Fisioterapeutas